(MnO/Mn3O4)-NiAl nanoparticles as smart carbon resistant catalysts for the production of syngas by means of CO2 reforming of methane: Advocating the role of concurrent carbothermic redox looping in the elimination of coke. (14th December 2016) - Touahra, Fouzia; Sehailia, Moussa; Halliche, Djamila; Bachari, Khaldoun; Saadi, Adel; Cherifi, Ouiza
Abstract: Mixed oxide MnO/Mn3 O4 was successfully incorporated into NiAl hydrotalcite derived systems following an ionic exchange protocol via initial introduction of [MnY] 2− (Y = ethylenediaminetetraacetic acid (EDTA)) into the interlayer space of NiAl hydrotalcite structure. Upon calcination and subsequent reduction, the resulting material (NiAl-MnYcal. ) was successfully screened for its catalytic activity and carbon resistance in the reaction of CO2 reforming of methane; NiAl-MnYcal exhibited conversion values of CH4 and CO2 more than 93% while the ratio H2 /CO was close to 1 at 700 °C, an excellent combination to gain access to other long chained hydrocarbons following the Fischer-Tropsch approach. Most importantly, NiAl-MnYcal. showed 0.40 wt.% carbon deposition towards the end of the process of CO2 reforming of methane, potentially owing to the presence of an integrated carbothermic redox cycle based on Mn3 O4 /C/MnO/CO2 within the nickel rich catalyst as well as the large surface area of Ni particles obtained. All precursors and mixed oxides were characterized by Thermogravimetric analysis (TG), inductively coupled plasma atomic emission spectroscopy (ICP–AES), X-ray diffraction (XRD), Brunauer–Emmett–Teller method (BET), Fourier transform infrared spectroscopy (FTIR), temperature programmed reduction (TPR) and scanning electron microscopy (SEM). Analyses of the material demonstrated the formation of nano-sized particles containing mixed crystalline phases of Ni, NiO, MnO, Mn3 O4 and NiAl2 O4 . The catalytic results were also valorized against other catalysts (NiAlcal and MnAlcal ) synthesized via co-precipitation method. At 700 °C, NiAl-MnYcal displayed ca. 10% more conversion of CH4 and CO2 than that of NiAlcal. ; the ratio H2 /CO was 0.99, 6.4% higher than that of NiAlcal. . No reaction of CO2 reforming of methane took place in the absence of Ni. Graphical abstract: Highlights: (MnO/Mn3 O4 )-NiAl nanoparticles were successfully synthesized from hydrotalcite precursors. The material exhibited more than 93% in CO2 and CH4 conversions in CO2 reforming of methane at 700 °C. Carbon deposition calculated using thermogravimetric analysis was at its minimum (0.4 wt.%). The active phases MnO, Mn3 O4 and Ni 0 were clearly identified by XRD prior to and after the reaction. We envisage a carbothermic cycle based on Mn3 O4 /C/MnO/CO2 responsible for the elimination of coke.